Auditoría de gestión a la gerencia de finanzas de la empresa eléctrica regional del sur s.a matriz loja durante el periodo 01 de enero al 31 de diciembre del 2012 - Montaño Jiménez, Sandra Gabriela (2016)
This research work entitled "Auditing the Financial Management of Regional Utility Matrix Loja South SA for the period January 1 to December 31, 2012." Contains in its structure a detailed study of the reality of the company dedicated to distribute and sell electricity and thus provide electric service to customers, quality, reliability and security at the lowest cost energy. The objectives were designed to evaluate the internal control system, and the degree of compliance with regard to the objectives and goals established through the application of performance indicators for the components to be considered, submit an audit report management respetivas which contain the conclusions and recommendations are designed the same as you help a correct decision making to optimize institutional management. During the implementation of the components Auditing Human Resources, Financial Resources and Material Resources, where the various shortcomings that affect the management of management as they met, staff control does not guarantee the permanence of officials evaluated their jobs, the manual has not been updated functions, the trainings are not met in full. 6 The budget allocated by the state is not enough to fully cover the activities, the financial staff is not cautioned, credit notes are not recorded timely and distorting same bank balances books. Inventories of office supplies are not updated regularly, management does not have an integrated when entering accounting information system. The methodology used is consistent with the provisions of the Comptroller General through the Audit Manual as: Preliminary Knowledge, where a visit to the institution for observation of their activities performed daily, then we have the Planning , the same as is the review of information and documentation of the organization where we Execution findings and develops all necessary to support the conclusions and recommendations made in the audit report evidence is obtained and finally we have the Communication Result where Comments conclusions and recommendations aimed at improving the entity are presented. As concluded in the Finance, System implemented internal control is not efficient because it has violated several Rules of Internal Control, which in it caused no assigned activities properly fulfill each one of the officials.